Beyond Motivation: How Organizational Citizenship Behavior Translates Employee Enthusiasm Into Performance In The Garment Industry - Muhammad Rizki Firdaus; Ginanjar Indra Kusuma; Agung Suwandaru; Anandhayu Mahatma Ratri (University of Merdeka Malang, 2025)
This study investigate the structural relationships between work motivation, work enthusiasm, and employee performance within the competitive Indonesian garment industry, where a critical disconnection exists between positive employee attitudes and desired organizational outcomes. The novelty of this research lies in its focus on exploring the underlying mechanism connecting these psychological states to performance by investigating the mediating role of Organizational Citizenship Behavior (OCB) in this particular industrial and cultural context. A quantitative, cross-sectional design was employed, with data collected from 70 employees in the Malang garment industry via structured questionnaires. The hypothesized model was tested using Structural Equation Modeling (SEM). The results indicate that while work motivation and enthusiasm have significant direct positive effects on performance, their influence is also partially mediated by OCB. This implies that the translation of positive psychological states into tangible performance is critically dependent on employees’ engagement in voluntary, pro-social behaviors. Therefore, it is recommended that organizations adopt a holistic human resource strategy that not only fosters motivation but also actively cultivates and rewards organizational citizenship behaviors to unlock the full performance potential of their workforce.